2019
DOI: 10.1590/rbz4820180286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immunocastration on sex glands of male Mangulica (Swallow-bellied Mangalitsa) pigs

Abstract: The objective of this research was to study the effect of immunocastration on the morphometric characteristics of sex glands in male Swallow-bellied Mangalitsa pigs. The study included 24 animals (13 entire and 11 immunocastrated males). The research focused on the following traits: age at slaughter (days), live weight at slaughter (kg), growth rate (kg day −1 ), and morphometric testicle traits (volume, cm 3 ; weight, g; length, width, thickness, and circumference, mm). The efficacy of immunocastration was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In comparison to boars, all reproductive organs of immunocastrates were significantly lighter. These findings are in full agreement with several studies [49][50][51] which show a significant impact of treatment with Improvac ® on the development of the male genital tract. The different compartments, however, were affected to a various degree.…”
Section: Discussionsupporting
confidence: 93%
“…In comparison to boars, all reproductive organs of immunocastrates were significantly lighter. These findings are in full agreement with several studies [49][50][51] which show a significant impact of treatment with Improvac ® on the development of the male genital tract. The different compartments, however, were affected to a various degree.…”
Section: Discussionsupporting
confidence: 93%
“…As an alternative to surgery, immunological castration has its pros and cons (Bonneau & Weiler, 2019). According to scientific reports, immunological castration affects morphometric parameters of the testicles in male pigs (Gogić et al, 2019), and other reproductive organs (Škrlep et al, 2012). Histological changes in the tubules and the interstitial tissue of the testicle are also objective parameters of successful castration.…”
Section: Introductionmentioning
confidence: 99%
“…In an experiment with immunocastrated pigs, Andreo et al (2018) affirmed that there is individual variation in the antibody titers generated by the vaccine among animals due to factors such as genetics, nutritional status, age and stress at the time of application, which explains the fact that in the present study animals have different responses to treatment. Gogić et al (2019) with swine, which found a reduction of 28.9 to 54.4% in the testis volumes and weights of immunocastrated animals compared to control animals. According to Lents et al (2018) these reductions in testicular volumes can be attributed to a reduction in the diameters of seminiferous tubules and the reduced mitotic capacity of sperm cells after the application of the anti-GnRH vaccine.…”
Section: Resultsmentioning
confidence: 94%